Work-related fatalities involving emergency service workers in Australia, 1989-1992 : information from the second work-related fatalities study, 1989 to 1992 (National Occupational Health and Safety Commission, 1999)
Work-related fatalities involving emergency service workers in Australia were studied as part of a larger study of all work-related traumatic fatalities that occurred in Australia during the four year period 1989 to 1992. During this period, there were 37 employed and volunteer workers (25 employed; 12 volunteer) who were fatally injured while performing emergency service work. Another 15 bystanders were fatally injured as a result of the emergency service work of others. There were also five emergency service workers who were fatally injured while commuting. The work-related fatality rate for police officers was 11.3 deaths per 100,000 workers per year, compared with the all workforce rate of 5.5 deaths per 100,000 workers. Rates for other emergency service workers were not able to be determined. Common features of the fatal incidents involving emergency service workers included: - police officers: deliberate injury by a felon being apprehended, motor vehicle accidents while on rou